Optimization Of Sorbent System From Paper Mill Waste Short Fibers For Bioremediation Of Heavy Hydrocarbons In Soil (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The aim was to develop a new improved Sorbent system (S-S) from organic sorbent material, nutrients, biosurfactant and microbial cell producing it for bioremediation of heavy oil hydrocarbons in various soil types. New sorbent material (S-M) was developed from paper mill short waste fibers because it requires very low energy to manufacture and the production costs of this S-M is extremely low compared to similar products in the market. S-M has good sorption characteristics for various oil products, is fully biodegradable, can be applied at sensitive environmental areas. S-M can be combined with microorganisms producing biosurfactant. The goal of investigations was to optimize S-S composition to minimize the leakage of heavy hydrocarbons to deeper soil layers or ground water. The optimal composition of S-S for all types of soil was determined: S-M 86.3-89.3%, microorganisms producing biosurfactant ≥ 107 CFU/g, biosurfactant solution – 3%, nutrients (nitrogen and phosphorous) 0.5 and 0.2%. Recommended optimal S-S moisture is 7%.